Biofuel from Co-pyrolysis of Solid Tire Waste and Rice Husk. (March 2017) - Hossain, M.S.; Islam, M.R.; Rahman, M.S.; Kader, M.A.; Haniu, H.
Abstract: In this study the conversion of solid tire waste and rice husk into biofuels and chemicals by externally heated fixed-bed co-pyrolysis reactor have been taken into consideration. The solid tire waste and rice huskwere characterized through proximate and ultimate analysis, gross calorific values and thermo-gravimetric analysis to investigate their suitability as feedstock for this consideration. The collected solid tire waste chipped and then mixed with rice husk at different blends. The mixtures of solid wastes were fed into the reactor and the products were oil, char and gases. The liquid and char products were collected separately while the gas was flared into the atmosphere. The process conditions were varied by the percentage oftire in the blends at reactor temperature 450 °C. The variation of tire waste in feed blends was found to influence the product yields and feedstock to oil energy conversion efficiency (FOECE) significantly. The maximum liquid yields were 52wt% for50% tire and 50% rice husk blend at reactor temperature 450 °C for zeroN2 gas flow, feed size 1800-2300 μm for rice husk and 2cm×1cm×1 cm for tire waste and running time 60 min. Liquid products obtained at these conditions were characterized by physical properties, chemical analysis and fractional distillation. The results show that it is possible to obtained liquid products that are comparable to petroleum fuels and valuable chemical feedstock from the selected wastes if the pyrolysis conditions are chosen accordingly.